2011
DOI: 10.1590/s1516-14392011005000043
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of reduction of stress shielding in laser coated hip prostheses

Abstract: The increasing use of titanium alloys as biomaterials can be attributed, among other factors, to their low Young modulus compared to other alloys with similar mechanical strength. However, Ti-6Al-4V alloy, the alloy most widely used in implants, has a stiffness of about 110 GPa, which is much higher than the typical stiffness of 20 GPa of human bone. In the specific case of hip arthroplasty, this difference in stiffness reduces the load imposed on the femur through the stress shielding phenomenon, which, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Different shapes of the pins may have reduced the exposure of different parts of the pins to body fluids and multinucleate cells, and thus, significantly reduced solution-mediated dissolution and cell mediated resorption [ 16 ]. Furthermore, it has been demonstrated that load bearing incites the biodegradation of biomaterials [ 17 , 18 ]. Based on the stress shielding, the bioceramics possessing greater stiffness are likely to bear larger loads than the bioceramics possessing less stiffness [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different shapes of the pins may have reduced the exposure of different parts of the pins to body fluids and multinucleate cells, and thus, significantly reduced solution-mediated dissolution and cell mediated resorption [ 16 ]. Furthermore, it has been demonstrated that load bearing incites the biodegradation of biomaterials [ 17 , 18 ]. Based on the stress shielding, the bioceramics possessing greater stiffness are likely to bear larger loads than the bioceramics possessing less stiffness [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that load bearing incites the biodegradation of biomaterials [ 17 , 18 ]. Based on the stress shielding, the bioceramics possessing greater stiffness are likely to bear larger loads than the bioceramics possessing less stiffness [ 17 ]. The lower degradable rate of the “neck” part could be attributed to the lower compressive strength of the “neck” part in comparison to circumference surfaces and cusp.…”
Section: Discussionmentioning
confidence: 99%
“…An adequate elastic modulus of the coating layer is important as it affects load distribution and stress shielding at the interface layer between a coated implant and the surrounding bone [ 13 ]. Also, the success of a particular implant in vivo depends on adequate adhesion of the coating layer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mismatch of the mechanical properties, between scaffold and surrounding tissue, can lead to stress shielding around the scaffold and subsequently inhibit tissue ingrowth or cause implant loosening [ 10 , 11 ]. Therefore, the mechanical properties of the implants acting as scaffolds for bone ingrowth should be adapted to the mechanical properties of the surrounding tissue [ 12 ].…”
Section: Introductionmentioning
confidence: 99%